ADSORPTION ISOTHERMS OF LEAD ION BY CHITOSAN FROM SHRIMP SHELL - Yenni Rahmadani; Fauzia Rozani; Azimatur Rahmi; Muslim Suardi (LLDIKTI Wilayah X, 2017)
The adsorption activities of chitosan from dried shrimp shells Metapenaeus monoceros (Fabrices) has been studied by analyzing its ability to remove lead ion from aqueous solution. This process including (i) isolation of chitosan from shrimp sells by Â deproteinization with NaOH, demineralization by adding HCl solution, decolorization with sodium hypo chloride and deacetylation by adding NaOH, (ii) studied of interaction between chitosan and Pb. The qualitative and quantitative method were used to analyses this chitosan. The isolate of chitosan has 72.39 % degree of deacetylation. This isolate was added into lead solution 10 â€“ 1000 mg/l at pH 5. Furthermore, the solutions were shaken during 24 hours. After separation of chitosan from solution, the filtrate was identified by using Atomic Adsorption Spectrophotometric. The results showed that chitosan from dried shrimp shells can used as adsorbent of lead ion at pH 5 which followed Freundlich isotherm (r > 0.95).